Intellectual disability health content within medical curriculum: an audit of what our future doctors are taught. Issue 1 (December 2016) - Trollor, Julian; Ruffell, Beth; Tracy, Jane; Torr, Jennifer; Durvasula, Seeta; Iacono, Teresa; Eagleson, Claire; Lennox, Nicolas
Abstract Background There is a high burden of unmet health needs for people with intellectual disability. Despite experiencing significantly higher rates of morbidity and mortality compared with the general population, this group faces greater barriers to accessing healthcare. While increasing workplace capacity is one way to reduce this inequitable access, previous research indicates a scarcity of undergraduate teaching in intellectual disability. The aim of the study was to determine the extent and nature of intellectual disability content currently offered within medical degree curricula. Methods All Australian universities (n = 20) providing accredited medical training were invited to participate in a two-phase audit via an email invitation to the Dean of each medical school. The Dean's delegate from 14 medical schools completed Phase 1, which involved a questionnaire or telephone interview about the overall medical course structure. Unit coordinators and/or teaching staff from 12 medical schools completed Phase 2, which involved an online survey about intellectual disability content within the curriculum. Results In Australia, medical school curricula contain a median of 2.55 h of compulsory intellectual disability content. The majority of universities only offer a small amount of compulsory content. Of compulsory units, intellectual disability teaching is minimal in sexual health and emergency medicine (only one unit offered in one school for each). Topics of key relevance in intellectual disability health such as human rights issues, interdisciplinary team work and preventative health are poorly represented in intellectual disability teaching. Elective content varies markedly across universities (1 to 122 h), but emergency medicine, women's health, men's health and many other specialist medicine areas are not represented. Inclusive practice is inconsistent in degree and nature, but a majority of universities (nine) involve people with intellectual disability in the development or delivery of content. Conclusions There is a mismatch between the considerable unmet health needs of people with intellectual disability and the inconsistent teaching within medical schools. Future doctors will be better equipped to support the health and wellbeing of people with intellectual disability if curricula are enhanced in this area.